2015
DOI: 10.1021/acs.langmuir.5b01406
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Versatility in the Self-Assembly of Val-Ala and Ala-Val Dipeptides

Abstract: Since the discovery of dipeptide self-assembly, diphenylalanine (Phe-Phe)-based dipeptides have been widely investigated in a variety of fields. Although various supramolecular Phe-Phe-based structures including tubes, vesicles, fibrils, sheets, necklaces, flakes, ribbons, and wires have been demonstrated by manipulating the external physical or chemical conditions applied, studies of the morphological diversity of dipeptides other than Phe-Phe are still required to understand both how these small molecules re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…Oligopeptides that consist of amino acids with aliphatic side chains have received less attention 21, 22. Furthermore, outside of tripeptide assemblies, there have only been a few studies which focused on oligopeptide sequences that are slightly extended in length (4–8 amino acids).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oligopeptides that consist of amino acids with aliphatic side chains have received less attention 21, 22. Furthermore, outside of tripeptide assemblies, there have only been a few studies which focused on oligopeptide sequences that are slightly extended in length (4–8 amino acids).…”
mentioning
confidence: 99%
“…[21,22] Furthermore,outside of tripeptide assemblies,t here have only been af ew studies which focused on oligopeptide sequences that are slightly extended in length (4-8 amino acids). In af ew cases,t hese studies have been based on short peptide fragments of larger polypeptides already known to self-assemble into nanostructures,s uch as NFGAIL [5,23] (fragment of human islet polypeptide) and KLVFFAE [24] (part of amyloid b [16][17][18][19][20][21][22] ). Most recently,P appas et al utilized ad ynamic combinatorial peptide library with dipeptide inputs and discovered that sequences of four residues (W4, F2L2) and six residues (F6, L6) formed higher-order assemblies.A dditionally,t he eight-residue FDFSFDFS sequence was also able to form aself-supporting hydrogel.…”
mentioning
confidence: 99%
“…[31] It was shown that differences in the interactions between peptides and solvent molecules lead to the formation of different peptide structures. The morphology of 2 is similar to Val-Ala obtained from pyridine.…”
Section: Powder Xrdmentioning
confidence: 99%
“…Nile red stains nanosheets composed of peptoids. [31,40] In the dipeptides where intramolecular hydrogen bonds are unlikely to occur, intermolecular hydrogen bonding and hydrophobic interactions are important determinants of superstructures. Clearly, the surface of the nanotubes composed of aliphatic groups, are hydrophobic enough for a lipophilic dye such as Nile red to bind.…”
Section: Interaction Of Fluorescent Dyes With Peptide Aggregatesmentioning
confidence: 99%
See 1 more Smart Citation